2007
DOI: 10.1016/j.jvs.2007.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Long-term durability of open abdominal aortic aneurysm repair

Abstract: Open repair remains a safe and durable option for the management of abdominal aortic aneurysms, with an excellent associated 10-year survival in patients who undergo operation at 75 years of age or younger. In addition, the freedom from graft-related reintervention is superior to that of EVAR. Finally, continued surveillance after open repair is appropriate and should be directed toward the detection of other aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 28 publications
7
79
0
3
Order By: Relevance
“…Hertzer et al reported much less graft-related complications(0.4%) with 5-year follow-up, although only clinically evident (as opposed to computed tomography scan-detected) events were considered (Hertzer et al, 2002). Conrad et al described a cohort of 540 open non-ruptured AAA repairs (Conrad et al,2007). 152 Of them had follow-up CT scans which revealed 13 graft-related complications identified in 11 patients, including 7 anastomotic pseudoaneurysms (4 proximal and 3 distal).…”
Section: Incidence Of Anastomotic Aneurysmmentioning
confidence: 99%
See 2 more Smart Citations
“…Hertzer et al reported much less graft-related complications(0.4%) with 5-year follow-up, although only clinically evident (as opposed to computed tomography scan-detected) events were considered (Hertzer et al, 2002). Conrad et al described a cohort of 540 open non-ruptured AAA repairs (Conrad et al,2007). 152 Of them had follow-up CT scans which revealed 13 graft-related complications identified in 11 patients, including 7 anastomotic pseudoaneurysms (4 proximal and 3 distal).…”
Section: Incidence Of Anastomotic Aneurysmmentioning
confidence: 99%
“…Conrad et al performed CT scanning of 152 of 540 open repairs. There were four graft limb occlusions in the bifurcated grafts that were treated with open thrombectomy and revision of the distal (femoral) anastomosis (Conrad et al, 2007). The Dutch Randomized Endovascular Aneurysm Repair (DREAM) trial followed 178 open and 173 EVAR cases and found a total of 3 occlusions after open repair and 12 after EVAR (De Bruin et al, 2011).…”
Section: Graft Occlusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have achieved significant technological advances since the first generation of aortic stents, recent information from late postoperative follow-up have shown a significant percentage of complications requiring surgical reintervention. The reason for treatment failure, in many cases, is still connected to the endoprosthesis used (type III leakage) [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple comorbidities, previous operations, and the need for suprarenal cross-clamping place this patient population at high risk for reoperation. 1 During a 5-year period, Conrad and co-authors 2 reported a 24% incidence of late aortic aneurysm proximal to the site of repair in 540 patients who had undergone elective open AAA repair.…”
mentioning
confidence: 99%